Analisis Tingkat Layanan Jalan Berdasarkan Manual Kapasitas Jalan Indonesia 1997 : (Studi Kasus Jalan Residen Abdul Rozak Palembang Pada 2022) - Wardatul Jamilah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
The aim of this research is to determine the level of service on Resident Abdul Rozak's roads in 2022 based on the 1997 Indonesian Road Capacity Manual by determining the volume of vehicles on Resident Abdul Rozak's roads, assessing the influence of side obstacles on the sections and determining the level of service on Resident Abdul Rozak's roads. This research is quantitative descriptive research. Data collection uses field observations and documentation. Data analysis uses the 1997 Indonesian Road Capacity Manual. The results of the data analysis are used to determine the traffic volume on the Resident Abdul Rozak road. The results show that the volume of traffic flow on the Resident Abdul Rozak road on Thursday, December 8 2022 in the north direction is an average of 1,426 pcu/hour and in the South direction an average of 1,640 pcu/hour, while on Saturday 24 December 2022 the North volume was an average of 1,562 pcu/hour and in the South direction an average of 1,350 pcu/hour. Side resistance is in the low category with an average value of 244, 925 where the condition of side resistance is not too influential. The level of service is in category E with a value of 0.901, where conditions on that day of the city's roads were unstable, at full capacity.